Preparation of poly(styrene‐co‐isobornyl methacrylate) beads having controlled glass transition temperature by suspension polymerization. Issue 1 (3rd November 2012) - Zhang, Bing; Ma, Yuhong; Chen, Dong; Xu, Jingnan; Yang, Wantai
Abstract The styrene (St) and isobornyl methacrylate (IBMA) random copolymer beads with controlled glass transition temperature (Tg), in the range of 105–158°C, were successfully prepared by suspension polymerization. The influence of the ratios of IBMA in monomer feeds on the copolymerization yields, the molecular weights and molecular weight distributions of the produced copolymers, the copolymer compositions and the Tgs of these copolymers was investigated systematically. The monomer reactivity ratios were r1 (St) = 0.57 and r2 (IBMA) = 0.20 with benzyl peroxide as initiator at 90°C, respectively. As the mass fraction of IBMA in monomer feeds was about 40 wt %, it was observed that the monomer conversion could be up to 90 wt %. The fractions of IBMA unit in copolymers were in the range of 35–40 wt % and Tgs of the corresponding copolymers were in the range of 119.6–128°C while the monomer conversion increased from 0 to greater than 90 wt %. In addition, the effects of other factors, such as the dispersants, polymerization time and the initiator concentration on the copolymerization were also discussed. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013